1995
DOI: 10.1002/jsfa.2740690113
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state fermentation of Lathyrus sativus seeds using Aspergillus oryzae and Rhizopus oligosporus sp T‐3 to eliminate the neurotoxin β‐ODAP without loss of nutritional value

Abstract: Abstract:The presence of a neurotoxic amino acid, 3-N-oxalyl-~-2,3-diaminopropanoic acid (8-ODAP), in the seeds of grass pea (Lalhyrus satiuus) is the cause of an irreversible spastic paraparesis, neurolathyrism, after overconsumption. This is a negative factor in an otherwise very tasty, nutritious, easily cultivated and hardy food crop in Asia and Africa. The reduction of 8-ODAP to less than 10% of the original content has been reached by fermenting L satiuus Jamalpur seeds with Aspergillus oryzae NRRL 1988 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…Trypsin inhibitors activity was determined following the method described by Kakade et al (1974), β-ODAP concentration was determined by the HPLC method (Kuo et al 1995).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Trypsin inhibitors activity was determined following the method described by Kakade et al (1974), β-ODAP concentration was determined by the HPLC method (Kuo et al 1995).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Performance of fish in the rations containing similar levels of unfermented GPS was inferior to those reared on fermented ones. The results of the present study also indicated that bacterial fermentation improves the nutritive value of GPS [22]. Nutritionally, it is tasty and protein-rich [6], but the presence of a variety of anti-nutritional factors hinders its free nutritional utilization [5].…”
Section: Resultsmentioning
confidence: 79%
“…Ruiz-Terán and Owens (1996) and Bau et al (1994) did not observe any changes in ash level comparing soybeans prepared to fermentation and tempeh. However, Bau et al (1994) and Kuo et al (1995) obtained increased amount of ash in tempeh made from rapeseed meal and grass pea, respectively. Therefore it seems probable that the observed ash contents could be the consequence of rearrangement of tempeh composition following the degradation of other constituents.…”
Section: ) Protein Content and In Vitro Bioavailability Amino Acidsmentioning
confidence: 92%
“…chinensis (Institute for Microbial, Taichung, Taiwan) using for grass pea seeds fermentation (Kuo et al, 1995;Kuo et al, 2000) was grown on malt extract agar. Spores were harvested after 12 days with sterile saline supplemented with peptone (0.01 g/L) and Tween 80 (0.1 mL/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation